(untitled) (American Journal of Islam and Society, 2002)
Amira El-Azhari Sonbol has written an outstanding socio-politico-eco nomic analysis of the Egyptian government and society over the last three centuries. This book brilliantly debunks the oriental despot model of analysis that has been imposed on scholarly studies of Muslim societies. She achieves this with the aid of a "study of popular discourse." She emphasizes the need to relearn what culture is all about by examining how Egyptians see themselves and their own relationships. She finds that Egyptian society has not been static, waiting to be transformed from the outside, but dynamic, following its own cultural evolution. Along the way, she notes the importance of distinguishing Islamic revival from radicalism and terrorism. Sonbol argues that eighteenth-century Egypt has been misunderstood, forced into the absolutist mold that more properly characterizes today’s Egypt. Eighteenth-century Egypt reflected "social maneuverability" and the "rule of law." In the 19th and 20th centuries the Egyptian state sought, with partial success, to establish itself as the "active creator" of law and order. A new form of mercantilism emerged that went beyond the mere control of imports and exports to the manipulation of all aspects of production and exchange to the benefit of the elites. In the Nasser era, elements of socialism and nationalism were employed in the advancement of what was actually a form of state capitalism, in which the elites sought to extract rent from their hold on power. It was a feudal compact, in which the state’s "right" to political allegiance was "reciprocated by the state’s ’duty’ to guarantee the security of the nation and provide its people with" the necessities of life. Sonbol critiques the translation of khassa as elite and ’ammah as general pub I ic. The khassa are the people of power, wealth, and distinction, only one part of which retains hegemony at any given time. The khassa are too diverse (ruling elites, the military, and the business classes) to be considered an aristocracy. From time to time the ulema, the intellectuals and the pro fessionals have been their allies in legitimizing their power. The so-called modernization of the Arab world has only been a strengthening of ...